Maria Graham: a performatividade nos diários de viagens da América do Sul no século XIX - Silva, Any Marry (2019)
In this research we analyse the travel writer Maria Graham (1785–1842), an English woman whose books were published during her lifetime, having works on translations, novels, and travel memoirs. The focus of this research were the journals regarding South America: Journal of a Voyage to Brazil, and residence there, during part of the years 1821, 1822, 1823 (1824) and the Journal of a residence in Chile during the year of 1822; and the Voyage from Chile to Brazil in 1823 (1824), in which she narrated the social, cultural and political questions about the composition of South America’s Independences, with the particularity of her English imperialist discourse combined to her construction as a woman. In order to do so, the concept of Performativity is used to understand how gender was a big part of her writing choices and how she composed her stories in the journals. We sought to understand the reasons why Graham supported the processes of Independence in Brazil and Chile and how the writer constructed these journals from her perspective as a woman who writes not only her story as a traveller, but also about the history of those countries she visited in the early nineteenth century